Transformation Of Batik As A Symbol Of Nationalism And National Identity - Desma, Sahwa (Kamara Journal, 2024)
Batik, as Indonesia's cultural heritage, has gone through a significant transformation, making it a symbol of nationalism and deep national identity. As a cultural expression that reflects the diversity of ethnicities, religions, and customs in Indonesia, batik is now not only used in state events, but also in everyday life. Each batik motif originating from various regions contains rich philosophical and historical meanings, illustrating the richness of Indonesia's local culture. The recognition of batik by UNESCO as an Intangible Cultural Heritage in 2009 further strengthened its position as a symbol of national pride that is recognized at the international level. The main challenge facing batik is to maintain its authenticity and quality amidst globalization and the rise of mass production that does not follow traditional batik techniques. Therefore, it is important to preserve batik through education and training of batik skills for the younger generation, as well as conducting sustainable promotion in the global market. Batik also provides a significant economic impact, creating jobs for local artisans and introducing Indonesian culture to the international world. With design and technique innovations that still emphasize traditional values, batik can continue to survive and thrive in the modern era, playing an important role in strengthening Indonesia's cultural identity at the global level.